Determinan Pengeluaran Rokok Elektrik di Kota Bandung - Sihaloho, Estro Dariatno; Hardiawan, Donny; Akbar, Mochamad Thoriq; Rum, Irlan Adiyatma; Siregar, Adiatma Y. M. (UI Scholars Hub, 2020)
the Convenience Sampling and Slovin formula, interviews 200 users of e-cigarettes in Bandung. This paper uses Multiple Linear Regression (MLR) with STATA 12. Total expenditure per month in electronic cigarettes, the price of electronic cigarette suction machine tools, motivation in using electronic cigarettes, the amount of electronic cigarettes liquid taste, knowledge about the risk of using electronic cigarettes, and the status dual user of conventional cigarettes and electronic cigarettes are has been used as variables in this research. The regression result shows that the price of electronic cigarettes, motivation to use electronic cigarettes, the amount of electronic cigarettes liquid taste are positively and significantly correlated with the total expenditure per month for electronic cigarettes in Bandung. In the other hand, knowledge about the risk of using electronic cigarettes not significantly reduces electronic cigarette expenditure. This study also finds that the status of dual users of electronic cigarettes and conventional cigarettes has a negative but not significant effect on electronic cigarette expenditure. To reduce the use of electronic cigarettes, the government needs to increase health campaigns regarding the dangers of electronic cigarettes.Even the government must bans the use of electronic cigarettes because knowledge about electronic cigarettes risk has insignificant effect to reduce consumption of electronic cigarettes.